Differences In Teeth And Mouth Hygiene By Brushing Teeth Using A Mirror And Without A Mirror In Class V And VI Students Of SDN 12 Koto Tinggi - Anses Warman; Arnetty Arnetty; Ika Ifitri (Lembaga Pengembangan Kinerja Dosen, 2024)
Dental and oral diseases that are commonly found in Indonesia are dental caries and swollen gums. Children aged 10-14 years in West Sumatra experienced dental caries by 41.47% and swollen gums by 11.30% caused by plaque. Plaque prevention is done by brushing your teeth thoroughly and regularly. Mirror As a tool for brushing teeth can see the entire surface of the teeth so that maximum accuracy and cleanliness are obtained. This study aims to determine the difference between brushing teeth using mirror aids and without mirror aids in grade V and VI students of SDN 12 Koto Tinggi. Research method